Codifying African dance: the Germaine Acogny technique and antinomies of postcolonial cultural production. Issue 1 (2nd January 2019) - Swanson, Amy
Abstract : The French-Senegalese choreographer Germaine Acogny is deemed to be the first to develop a dance technique that is both 'African' and 'universal.' Following her teaching certification training from 2010 to 2013, a growing body of dancers around the world practice the Germaine Acogny Technique as it is no longer only foundational at her École des Sables in Senegal but also taught overseas by certified instructors. Initiated by a confrontation with the restrictions of classical ballet and as a way to valorize and professionalize African dances, the technique may be considered a site of decolonial cultural production. Yet, it must contend with continued Euro-American economic and immaterial dominance. Based on ethnographic research at École des Sables, this paper examines antinomies inherent to the Acogny Technique. Using theories of postcolonial cultural production and consumption, I demonstrate that the technique sustains a critique of power structures embedded within Western-derived dance techniques while constituting a shared, meaningful movement vocabulary for Pan-African dancers. At the same time, it capitalizes on certain colonialist signifiers of a differentiated Africa, a tendency all but required for survival in the late capitalist global economy.